2016
DOI: 10.1212/wnl.0000000000003036
|View full text |Cite
|
Sign up to set email alerts
|

History of multiple sclerosis in 2 successive pregnancies

Abstract: Our work provides original data on the evolution of successive pregnancies in MS, showing a similar (and even lower) disease activity in the second pregnancy. There was no correlation of activity in successive pregnancies. Therefore, counseling of women with MS who consider having a second baby should be the same as for the first one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…The effect of breastfeeding on postpartum relapse risk has been controversial, with some studies supporting a protective effect, 192,200,201,203,204 while others have not. 5,119,199,205212 There is no evidence to suggest a harmful effect of breastfeeding on MS relapse risk, which is important given the many benefits of breastfeeding to the infant and mother. 170 A recent systematic review and meta-analysis included 24 studies evaluating the association between breastfeeding and postpartum MS relapses, of which 16 had data available to pool.…”
Section: Breastfeeding and Postpartum Relapsesmentioning
confidence: 99%
“…The effect of breastfeeding on postpartum relapse risk has been controversial, with some studies supporting a protective effect, 192,200,201,203,204 while others have not. 5,119,199,205212 There is no evidence to suggest a harmful effect of breastfeeding on MS relapse risk, which is important given the many benefits of breastfeeding to the infant and mother. 170 A recent systematic review and meta-analysis included 24 studies evaluating the association between breastfeeding and postpartum MS relapses, of which 16 had data available to pool.…”
Section: Breastfeeding and Postpartum Relapsesmentioning
confidence: 99%
“…Recently, a study comparing disease activity between the first and second pregnancies in a group of women with MS revealed similar disease activity. The above study indicated that the risk of relapses after the second pregnancy does not correlate with the outcome of the previous pregnancy .…”
Section: Discussionmentioning
confidence: 74%
“…This could be due to the fact that, if MS women were generally advised to consider pregnancy in a quiet period of the disease, women who experienced a relapse during a first pregnancy or after delivery may fear a similar outcome and be discouraged from considering a second pregnancy. In line with this, it is likely that women with MS with multiple pregnancies are also those with milder MS [31]; assuming that higher disease activity is related to worse long-term disability, they could have better long-term clinical outcomes. Furthermore, it should be highlighted that pregnancy is a well-circumscribed biological event in a long history of disease and that our patients had heterogeneous MS characteristics and DMT exposures before and after pregnancy, which complicates our evaluation of outcomes.…”
Section: Discussionmentioning
confidence: 90%